LANGUAGE LEARNING STRATEGIES OF NON-ENGLISH MAJOR STUDENTS IN DEVELOPING THE STUDENTSâ ORAL COMMUNICATION - Atbar, Mustahrim; Atmowardoyo, Haryanto; Weda, Sukardi (ELT WORLDWIDE, 2015)
Abstract Developing oral English communication proficiency for English major students is something usual, but for non-English major students who required to be proficient in oral English communication is obviously unusual. The questions that might arise are what strategies they apply to be proficient, how they apply those strategies and what makes those strategies useful or valuable for them. Therefore, the research questions for this problem are (i) What learning strategies are used by Civil Aviation Safety and Engineering Academy (CASEA) students in developing oral English communication? (ii) How do learning strategies facilitate CASEA students to be successful in English oral communication? (iii) What conditions are valuable for developing CASEA studentsâ English oral communication? The research aims at (i) Examining the learning strategies used by CASEA students in learning English. (ii) Exploring the ways learning strategies facilitate the CASEA studentsâ English oral communication. (iii) Exploring the conditions which valuable for developing studentsâ English oral communication. The research is applying qualitative research in the form of case study. The results of this study reveal that (i) the cadets in CASEA Makassar employed five strategies to develop their oral communication proficiency namely preparing production strategies, encouraging production strategies, effective production strategies, comprehension reaction strategies, and reinforcing comprehension strategies. (ii) Each of the employed strategies was facilitated the students to be proficient in oral English communication in certain way. It starts from collecting and organizing ideas (by preparing production strategies), lowering tense (by encouraging production strategies), covering limitations (by effective production strategies), understanding peopleâs ideas (by comprehension reaction strategies), and ensuring comprehension (by reinforcing comprehension strategies). (iii) Developing English oral communication can be maximal by the support of six conditions both internally and externally. The conditions are the presence of (1) certain motivation types, (2) extroverted personality, (3) prior English experience and preference in an English skill or element, (4) institutional policies, (5) supportive atmosphere, (6) media. Keywords: learning strategies, develop, oral communication, CASEA Makassar